(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
This article provides a detailed review of the morphological aspects of the APUD system in the intestinal epithelium, as well as the mechanisms underlying cellular specialization. The APUD system, a component of the gastroenteropancreatic endocrine system, comprises endocrine and neuroendocrine cells involved in regulating various physiological processes